Analysis of Phonological Errors in Reading Qasidah Burdah at Darul Falah Islamic Boarding SchoolTambak Sumur Sidoarjo Indonesia - Rohmatika, Nur (Journal of Arabic Language Studies and Teaching, 2023)
This study aims to describe the phonological errors of students of the Salafiyah Islamic boarding school, Darul Falah 42, Tambak Sumur, Sidoarjo. In addition to explaining the error, it also seeks the underlying causes or factors for the errors in the pesantren students to provide solutions to help improve the following learning process. In collecting data, researchers used listening, note-taking and recording techniques. In addition, researchers also use observation techniques, interviews, and also documentation. The research method uses a qualitative descriptive method. The phonological errors of the students were found in two groups of sounds, namely the group of throat sounds (الحلق) and the group of sounds of the tongue (اللسان). In this study, two causes or factors of error were found, namely linguistic factors and non-linguistic factors—the different alphabetical characters between Arabic and Indonesian caused the error. The non-linguistic factors include lack of self-confidence, reading comprehension, and mother tongue interference. Then, the researchers provide several solutions to help improve the subsequent learning process, namely that students should increase their enthusiasm for learning and improve their reading, teachers should pay special attention to students who are not fluent in reading Arabic literature, and teachers should provide recitation reviews for every student’s mistakes.